Características físico-qímicas da carne de caprinos submetidos a diferentes níveis de substituição do leite por soro de queijo durante o aleitamento - Ribeiro, M. N.; Pimenta, E. C.; de Almeida, C. C.; Costa, R. G.; do Nascimento, J. C. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1997)
Fifty six crossbred kids Parda Alpina x Gurgueia were separeted into four groups of 14 (seven male and seven female) and submited to four treatments with different levels of milk goat substitution by cheese serum. The treatments were : T1=milk goat (testify); T2=15% serum at 23 days and 33% at 55 days; T3=15% serum starting from 16 days, 33% on 23 days and 51% on 72 days of age; and T4=33% on 16 days and 69% of liquid diet in the final fase. At 92 days of age, all animals were slaughtered for carcass evaluation. Pallete were separeted from 20 male animals (five by treatment) and the physical and chemical analysis of the meat were realized using these materials. The studied characteristics were: total weight (TW), meat weight (MW), bone weigth (BW) of the pallete, and percentage of umidity (U), ashes (A), protein (P), fat (F) and pH of the pallete meat. There was significant effect of the treatment over F. Means of PW, A and BW were, respectively 491, 342 and 149.8 g. The meal represented 69,6% of total pallete weight. Means of U, A, P and F were 73, 1.0, 19 and 1.95%, respectively. The pH was 6.7. Results allow to conclude that only the fat percentage of the meat was modified, due to the administration of serun milk on the liquid diet of the kids, during the milking fase.
Physico-chemical traits of meat goat kids submitted to different levels of substitution of milk by serum of cheese during milking
Keywords: goats; carcass traits; meat quality